Effect of urban and rural resident basic medical insurance on catastrophic health expenditure in China - Wendi LIU; Zihan XU; Yan WANG; Ziyi WANG; Faqiang ZHANG; Kehu YANG; Xuefeng WEI; Xiuxia LI (Zhongguo gonggong weisheng)
ObjectiveTo analyze the impact of the urban and rural resident basic medical insurance on catastrophic health expenditure in Chinese residents. MethodsData from the 2020 China Family Panel Studies (CFPS) were used. Probit regression analysis was conducted with urban and rural resident basic medical insurance as the core variable. Propensity score matching (PSM) was taken to test for endogeneity. ResultsAt a threshold of 40%, the incidence of catastrophic health expenditure among Chinese residents was 13.88%. Probit model analysis showed that urban and rural resident basic medical insurance reduced the incidence of catastrophic health expenditure, with insured individuals having a 5.70% lower probability of experiencing catastrophic health expenditure compared to uninsured individuals. After addressing endogeneity, PSM results showed that urban and rural resident basic medical insurance still had a suppressive effect on the occurrence of catastrophic health expenditure. The impact of urban and rural resident basic medical insurance on reducing the incidence of catastrophic health expenditure differed significantly between western (β= –0.089) and eastern (β= –0.050) regions (both P<0.01). Age (β=0.035), education level (β= –0.011), urban-rural classification (β= –0.035), and regional classification (β=0.015) were also important factors influencing catastrophic health expenditure (all P<0.01). Conclusionsurban and rural resident basic medical insurance can effectively reduce the probability of catastrophic health expenditure among Chinese residents. Relevant departments can reduce the probability of catastrophic health expenditure by further refining urban and rural resident medical insurance policy design, improving the multi-level medical security system, and flexibly formulating regional medical insurance policies.